A Combination Blind Or Reaming Drill For Raise Construction - James E. Friant; L. "Andy" Anderson; Stephen N. Short (Society for Mining, Metallurgy & Exploration, 1985)
Since the introduction of "boxhole" drilling in South Africa in 1973, the concept of a blind raise, drilled upward from below, has become an accepted mining practice. A combination machine, capable of constructing raises to a mining level below, or blind raising upward from a single setup position adds a further dimension in versatility. A machine with these dual operating modes was designated by The Robbins Company as the 53R and was introduced into the Western Deep Level Mines, South Africa in 1984. The unit is powerful (200 hp) and compact (18,000 lbs., in a 10 ft x 4 ft 5 inch x 4 ft 6 inch package). This paper describes the design considerations for the new machine, provides field data from early trials, and looks briefly at its overall market and potential.